2018
DOI: 10.3389/fimmu.2018.01213
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Circulating Th17 and Regulatory T Cells in Alzheimer’s Disease: A Case Control Study

Abstract: The neuropathological hallmarks of Alzheimer’s disease (AD), i.e., neuritic plaques and neurofibrillary tangles, consist of beta amyloid peptides (Aβ) and hyperphosphorylated Tau. These are accompanied by reactive microglia and astrocytes in the vicinity of the neuritic plaques and by changes to the peripheral immune system, e.g., an increase of the pro-inflammatory cytokines IL-1β, IL-6, and TNF-α in the peripheral blood. To address a potential involvement of peripheral T helper cell (Th) subsets in AD, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 59 publications
5
68
2
2
Order By: Relevance
“…Recently, several studies have suggested that the frequencies of Th17 and the Th17/Treg ratio are enhanced in AD and/or MCI patients [56,57], which seems to contradict our results. However, our data show that the proportion of CD4 + IL-17A + Th17 cells was not altered among the WT, WT+IIV, AD and AD+IIV groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have suggested that the frequencies of Th17 and the Th17/Treg ratio are enhanced in AD and/or MCI patients [56,57], which seems to contradict our results. However, our data show that the proportion of CD4 + IL-17A + Th17 cells was not altered among the WT, WT+IIV, AD and AD+IIV groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, our results suggest that the higher IIV-induced Th17/Treg ratio is due to the decreased proportion of Tregs rather than higher Th17 proportion. Regarding the different Th17 proportion in AD patients reported in recent studies [56,57] and our results, a possible explanation for the differences is related to the different research subjects and immune cells (PBMC vs. spleen cells). It could be valuable to obtain similar data (Th17/Treg ratio) using different transgenic AD mouse models (3xFAD etc.)…”
Section: Discussioncontrasting
confidence: 57%
“…The frequency of IL4‐, IL17A‐, and IFN‐γ‐positive cells was analyzed in all three children groups, while IL21‐positive cells were analyzed only in children with CD (overt‐ and potential‐CD). Because it has been documented a downregulation of the expression of CD4 molecule on cell membrane after a strong stimulation (PMA/ionomycin mitogens) , the analysis of cytokine positive cells was performed in the gate of CD3 + CD8 + and CD3 + CD8 − T cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease of CD4+CD25 high T cells, an increase in CD4+Foxp3+ Tregs, but no changes in CD8+ T cell subsets, have been observed in Alzheimer’s dementia . Recently, a case control study reported an increase in circulating T helper 17 cells in the early stages of AD and an association of CD4+ CD127 low CD25+ regulatory T cells (Trges) with neurodegeneration marker Tau . In animal experiments, Tregs are shown to slow the AD‐like progression and restore cognitive function of APP/PS1 mice .…”
Section: Discussionmentioning
confidence: 99%